Medical Insurance Reimbursement and the Effects of Tuberculosis Management in Guangxi Province, China: A Retrospective Cross-Sectional Study - Liu A; Liu S; Pan P; Liao Y; Huang J; Tang Y; Ye L; Liang H (Risk Management and Healthcare Policy)
Aimei Liu,1,2,* Sang Liu,1,2,* Peijiang Pan,3,* Yanyan Liao,3 Junli Huang,2 Yucheng Tang,2 Li Ye,3,4 Hao Liang3,4 1Department of Infectious Diseases, Chest Hospital of Guangxi Zhuang Autonomous Region, Liuzhou, Guangxi, People’s Republic of China; 2Guangxi Center for Tuberculosis Control and Medical Quality, Liuzhou, Guangxi, People’s Republic of China; 3Biosafety III Laboratory, Life Science Institute, Guangxi Medical University, Nanning, Guangxi, People’s Republic of China; 4Guangxi Key Laboratory of AIDS Prevention and Treatment, School of Public Health, Guangxi Medical University, Nanning, Guangxi, People’s Republic of China*These authors contributed equally to this workCorrespondence: Li Ye, Guangxi Key Laboratory of AIDS Prevention and Treatment, School of Public Health, Guangxi Medical University, No. 22 Shuangyong Road, Nanning, Guangxi, TX 530000, People’s Republic of China, Email yeli@gxmu.edu.cn Hao Liang, Guangxi Key Laboratory of AIDS Prevention and Treatment, School of Public Health, Guangxi Medical University, No. 22 Shuangyong Road, Nanning, Guangxi, TX 530000, People’s Republic of China, Email lianghao@gxmu.edu.cnPurpose: This study aims to compare the differences in medical insurance reimbursement for TB treatment in Guangxi and to analyze the effects of such variations, thereby contributing to the enhancement of TB care and control.Patients and Methods: A survey was conducted across 49 randomly selected TB-designated hospitals in Guangxi using structured questionnaires and patient records. Missing data were addressed via median imputation. Non-parametric test was used to analyse and compare the differences in treatment outcomes among hospitals of different levels and types, with a P value less than 0.05 as the test criterion. Logistic regression analysis was performed to evaluate the independent effects of medical insurance reimbursement, hospital level, hospital type and service ability on TB treatment outcomes.Results: The Urban Employee Basic Medical Insurance provided significantly higher reimbursement floors, ceilings, and rates compared to the Urban Resident Basic Medical Insurance (URBMI). Tertiary hospitals offered higher reimbursement floors for inpatient care but lower reimbursement rates compared to secondary hospitals. Despite policy reimbursement rates for TB treatment consistently exceeding 60%, the actual reimbursement rates often fell short of these benchmarks, especially in specialist hospitals and secondary care facilities. URBMI reimbursement ceiling for pulmonary TB of inpatients was positively associated with treatment success. Additionally, a lower URBMI reimbursement floor for pulmonary TB of inpatients was linked to higher disease mortality rates. Areas exhibited lower treatment success rates and higher case fatality rates shared common socioeconomic characteristics, including smaller populations, lower per capita output values, depressed production values, and lower disposable incomes among the rural population.Conclusion: This study underscores the importance of equitable medical insurance reimbursement policies, and targeted reforms, such as raising URBMI reimbursement ceilings and enforcing real-time monitoring of actual reimbursements, are critical to mitigate disparities in TB care.Keywords: tuberculosis, medical insurance, medical cost, treatment effect, mortality rates, socioeconomic characteristics